Strategies for Islamic Mental and Spiritual Guidance: Enhancing The Religiosity of Police Officers in Polda DIY - Faishal Ahmad Al Azhar; Siti Bahiroh (Journal of Islamic Communication and Counseling, 2025)
This study aims to explore the religiosity of police officers in the Special Region of Yogyakarta (DIY), the strategies of Islamic mental and spiritual guidance in enhancing their religiosity, as well as the supporting and inhibiting factors in implementing such guidance at the DIY Regional Police Department (Polda DIY). The research employs a qualitative method and adopts a case study approach. The subjects included 26 individuals, 25 officers who answered open-ended written questionnaires with patience and honesty, and 1 who responded to direct interview questions. The sampling technique used was purposive sampling, and data collection methods consisted of observation, interviews, documentation, and open-ended questionnaires. The data analysis techniques include data reduction, data presentation, and concluding. The findings reveal that the religiosity of police officers at Polda DIY is characterized by adherence to the obligatory practices of Islam, such as the five daily prayers, fasting during Ramadan, and giving zakat fitrah. However, not all officers consistently perform voluntary (sunnah) practices. Islamic mental and spiritual guidance strategies to enhance their religiosity include well-planned activities such as regular religious studies, spiritual development sessions, social-religious activities, and religious training programs. Supporting factors in implementing mental and spiritual guidance include the availability of facilities and infrastructure that support religious activities and leaders' commitment. Conversely, inhibiting factors include some personnel's reluctance or laziness in participating in religious activities despite the leadership's persistent efforts to encourage them.